(untitled) (International Journal of Medical and Surgical Sciences, 2014)
Until the seventh week of human embryonic development of both sexes have very similar primordia of genitalia represented by two undifferentiated gonads two mesonephric ducts, which originate the male genital tract and two paramesonephric ducts develop the female genital tract. Genital tubercle, two labiouretrales folds and two labioscrotal folds: Externally the same basic elements that are distinguished in both sexes. From SRY gene expression that occurs during the eighth week a series of morphophysiological events leading establishing a clear sexual dimorphism starts. If the resulting gonad is a testis produced hormones induce masculinization of internal and external genitalia, as well as outline the breast. However, if an ovary is formed or not formed gonads, internal and external genitalia develop in female sense. Genetic sex is not always related to the differentiation of external genitalia or genital tract that is why we consider separately each. This article explores the morphological differentiation into male and female connection, as well as the molecular regulation of the gonads, genital tract and external genitalia.